Characteristics of Facial Skin Biophysical Parameters Among Medical Students in University of Mataram - Hidajat, Dedianto; Sari, Dian Puspita; Octora, Metta; Wedayani, Anak Agung Ayu Niti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Various studies have been widely published regarding the efficacy and adverse effects of facial care products with research populations from adolescent to young adults. However, it is necessary to first identify the characteristics of this parameters in the local population. The purpose of this study is to obtain an overview of the characteristics of the biophysical parameters of facial skin in a population of teenagers and young adults who tend to be active indoors, especially UNRAM medical students. This was an analytical observational study with a cross-sectional approach. Participants filled out questionnaires and followed procedures for examining facial skin biophysical parameters. The results of this study showed that from 147 participants, the average TEWL level was 8,99 g/h/m2; mean degree of erythema was 262,5; the average melanin index was 192,1 and the average sebum level was 192,1. Statistical analysis found that there was an association between gender and all facial skin biophysical parameters, a relationship between age and sebum levels and a relationship between daily activities in an air-conditioned room and the degree of erythema. With the data presented in this study, research related to facial skin biophysical parameters in similar populations can be developed further.